Variação espacial dos fatores que direcionam o desmatamento do cerrado - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
In the last decades the deforestation of Cerrado biome has reached alarming rates, being greater than the deforestation of the Amazon. Although the consequences of Cerrado deforestation are now well known, the study of its motivators is still insipient. Also, the existing studies consider that the causes of deforestation have the same relationships throughout the entire biome, which has been shown to be wrong, since anthropic processes, including deforestation, have a strong spatial structure, leading to different motivators to present different intensity of influence on deforestation in different regions. Thus, studies that take into account spatial structure in the deforestation process would be more adequate to evaluate their influence. In this study, was evaluated the spatial variability of the relationship between deforestation of the Cerrado biome and socioeconomic, environmental and structural variables, in order to provide information that considers local differences and helping the delineation of public policies more appropriate to each region. Geographically Weighted Regression (GWR) was used to calculate the relationship between deforestation and predictor variables. Rural agricultural credit, remaining native vegetation, mean precipitation, average distance between deforestation and highways, and mean slope presented the strongest relationship with deforestation in the Cerrado. GWR has shown that different regions have different relationships with deforestation. Thus, the public policies to curb deforestation in the Cerrado should be implemented in a way to address local peculiarities.
Keywords: Desmatamento; Cerrado; Regressão Geograficamente Ponderada; Políticas públicas; Deforestation; Cerrado; Geographically Weighted Regression; Public policy; CIENCIAS BIOLOGICAS::ECOLOGIA